An empirical analysis of the export-led growth (ELG) hypothesis in the Philippines - Ballester, Richard Emerson D. (The Philippine Review of Economics, 2013)
We reexamine the relationship between growth and exports of the Philippines for the period 1977-2009 using the methods of Sharma and Panagiotidis [2005] and Feder [1983]. With the shift in the current economic policy toward inclusive growth, we find it necessary to assess if indeed the export-led growth (ELG) hypothesis really worked for the country. Specifically, our research investigates the cointegration of exports, imports, and output using the Johansen cointegration test and the Breitung cointegration test; the Granger-causality between exports, investments, and output; and the impact of macroeconomic shocks by employing a vector autoregressive model. In summary, we find that the ELG hypothesis appears to be empirically unsupported for the Philippine case.